Tattooing tools and the Lapita cultural complex. Issue 1 (13th November 2017) - TORRENCE, ROBIN; KONONENKO, NINA; SHEPPARD, PETER; ALLEN, MELINDA S.; BEDFORD, STUART; KIRCH, PATRICK; SPRIGGS, MATTHEW
ABSTRACT: A use‐wear and residue study of 56 retouched obsidian flakes from seven Lapita sites in Papua New Guinea, Solomon Islands, and Vanuatu confirms that they had been used for tattooing. These specialised tools all bear one or more very small points formed by alternating retouch. A detailed comparison of use traces and pigments on these and 19 additional skin piercing tools analysed previously challenges the notion of homogeneity in cultural practices across the broad geographical range where Lapita pottery was used. The existence of shared innovations together with variation in the selection of pigments and the shape of the obsidian artefacts used for puncturing skin highlight a complex pattern of similarities and differences within this community of culture.